Aerodynamics of Bus Platooning under Crosswind - Aan Yudianto; I Wayan Adiyasa; Afri Yudantoko (Universitas Muhammadiyah Magelang, 2021)
The aerodynamic benefits of a vehicle in a platoon could be distracted by an imposed crosswind on it. The study aims to investigate the alteration of aerodynamic coefficient comprising drag force coefficient, lift force coefficient, side force coefficient, and pressure coefficient of buses traveling in a platoon by considering crosswind. A Computational Fluid Dynamic (CFD) simulation was carried out on a detailed bus model. Proposed meshing techniques were also offered. The investigation considered the yaw angle from 0Â° to 30Â° and inter-bus distances by proposed coefficient X/L from 0.05 to 1.25. The results in the changes in the aerodynamic performance of both buses were presented. The advantages of platoon configuration were described in more detail when no crosswind was considered in terms of the generated turbulence kinetic energy of the leading and following bus. The results indicated that a crosswind deteriorates aerodynamic benefits during the platoon. The inter-bus distance determines how the airflow around the bus behaves, leading to the variation in aerodynamic advantages experienced by buses. Comparison between the numerical study and experiment indicated a satisfactory correlation of results validation.